Understanding patients’ perceptions of uncomplicated low back pain: a theory-informed qualitative study using the Common-Sense Self-Regulation Model - Ruzycki, Shannon M.; Jasaui, Yamile; Mortazhejri, Sameh; Dowling, Shawn; Duquette, D’Arcy; Linklater, Stefanie; Mrklas, Kelly; Wilkinson, Gloria; Grimshaw, Jeremy M.; Patey, Andrea M. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Uncomplicated low-back pain (LBP), referring to LBP without symptoms that suggest an underlying medical or surgical cause, is a common and challenging problem for patients and primary healthcare providers. Multiple guidelines discourage the use of diagnostic imaging for uncomplicated LBP due to cost and lack of benefit; despite this, diagnostic imaging remains overused in this condition. Study of primary healthcare providers suggests that patient expectations contribute to imaging for uncomplicated LBP. Dedicated study of patient understanding and experiences of uncomplicated LBP is necessary to design interventions to reduce unnecessary diagnostic imaging. Methods In this theory-guided qualitative study, people with uncomplicated LBP were recruited for a semi-structured interview. The Common Sense – Self-Regulation Model (CS-SRM), a framework that explores the relationship between a patient’s perceptions, beliefs, and behaviors around their illness and the outcome of their illness, was selected to direct development of the interview guide and analysis. Higher-level themes were created to list patient-related drivers of unnecessary diagnostic imaging for uncomplicated LBP. Results Thirteen participants (7 female) had experienced uncomplicated LBP for a median of 5 years (IQR 2–20 years; range 1 to 30 years). Framework analysis based on the CS-SRM suggested that most participants understood their uncomplicated LBP as a permanent part of their lives, though some felt that the pain could be controlled or prevented. Participants shared a range of coping mechanisms, including social support, medication, and exercises. For most participants, uncomplicated LBP negatively affected their lives emotional wellbeing characterized by a sense of loss from missing life events due to pain. Nearly all participants had visited their primary care physician (n = 11) and most underwent diagnostic imaging (n = 8); however, participants generally reported that they had not requested diagnostic imaging (n = 8). Several participants reported that they wanted validation and symptom-management advice from their physician rather than diagnostic tests. Conclusions In contrast to other studies, we report that most patients with uncomplicated LBP in our setting did not request diagnostic imaging. Patient-facing interventions to address unnecessary diagnostic imaging for uncomplicated LBP may be more effective if they address illness conceptions identified in this study; for example, interventions should convey empathy by acknowledging patient worries, validating suffering, describing potential causes or triggers, addressing self-management strategies, and describing the natural history of uncomplicated LBP.